Zaščita pravic intelektualne lastnine v mednarodnem investicijskem pravu - Turšič, Domen (Podjetje in delo, 2021)
Due to the increasing number of international investment arbitrations, international investment law is becoming a more visible tool for the protection of intellectual property rights of foreign investors in the host state. After an overview of international intellectual property law and international investment law, the article focuses on the analysis of key issues for the success of a potential international investment arbitration claim of a foreign investor against a state due to state measures affecting intellectual property rights. The article analyses the conditions under which intellectual property rights can be a covered investment. It then proceeds with the analysis of substantive standards of protection of foreign investments that are relevant for investments affected by state measures negatively impacting intellectual property rights. The article approaches the issues from both a theoretical and a practical viewpoint, and therefore showcases the issues also through the prism of existing international investment cases, were state measures in question allegedly affected intellectual property rights.
Keywords: intellectual property law; international investment arbitration; international investment law; mednarodna investicijska arbitraža; mednarodno investicijsko pravo; patent; pravo intelektualne lastnine; trademark; znamka